USE OF MIND MAPS: TEACHING/LEARNING STRATEGY FOR THE CONSTRUCTION OF CONCEPTS IN A MEDICINE COURSE (CIPEEX, 2025)
The construction of scientific concepts represents one of the main difficulties faced in the teaching and learning process at all levels of schooling. This study aims to report the experience of using mind maps as a pedagogical strategy, highlighting the benefits observed by the students and the participants' perceptions regarding the use of this tool in the study of legislation (RDC No. 222/2018) concerning the adequate management of healthcare waste. The activities were carried out in a laboratory with first-period Medicine students, focusing on the elaboration of mind maps. The experience report is a research method that uses qualitative data collected from real events with the objective of understanding current phenomena within their own context. The process followed four fundamental stages: planning, organization, interactivity, and teaching. The application of this methodology not only facilitated the understanding of the addressed legislation but also sparked the teachers' interest in conducting research throughout the course, contributing to the consolidation of acquired knowledge. The obtained results indicate that the use of mind maps can be an effective tool to promote the construction of concepts and the interrelation of knowledge, favoring more significant and lasting learning. The reported experience suggests that the adoption of visual methods in teaching can improve the retention and practical application of knowledge, benefiting both the educational process and the training of future healthcare professionals.
Keywords: Mind Map; Interactivity; Learning; Teaching